Resurrection [videorecording (DVD)] - Semans, Andrew; Hall, Rebecca, 1982-; Kaufman, Grace; Esper, Michael; Roth, Tim (IFC Films, 2022)
A woman's carefully constructed life is upended when an unwelcome shadow from her past returns, forcing her to confront the monster she's evaded for two decades.